Cloud computing and SOA convergence in your enterprise : a step-by-step guide - Linthicum, David S., 1962- (Upper Saddle River, NJ : Addison-Wesley, 2010)
Chapter 1: Where we Are, How we Got Here, and How to Fix It. -- 2: Reaching for the Clouds. -- 3: Defining Clouds for the Enterprise. -- 4: Making the Business Case for Clouds. -- 5: Working from your Data, to the Clouds. -- 6: Working from your Services, to the Clouds. -- 7: Working from your Processes to the Clouds. -- 8: Bringing Governance to the Clouds. -- 9: Testing from SOA to the Clouds. -- 10: Defining Candidate Data, Services, and Processes for the Clouds. -- 11: Making the Move to Cloud Computing. -- 12: Moving Onward
Includes bibliographical references and index.
Keywords: Cloud computing; Service-oriented architecture (Computer science).; Web services